Active aging and health among older adults in China: a perspective based on downward intergenerational economic support - Liu Yuanfeng; Zhang Xu (Frontiers in Public Health, 2024)
IntroductionIn China, the rapid progression of population aging presents significant challenges to society and the economy, drawing widespread attention to the health conditions of older adults. While aging is often seen as a societal burden, the phenomenon of intergenerational economic support reveals the potential for older adults to continue playing an active role within their families. This study delves into how older parents’ financial support to their children can reciprocally influence their own health, exploring the potential non-linear relationships involved.MethodsThis research, utilizing data from the 2018 China Health and Retirement Longitudinal Study, employs instrumental variable techniques and cross-sectional threshold models to examine how financial support provided by older adults to their children affects their health. It particularly highlights the varied impacts of economic support on older adults’ health at different levels of support.ResultsThe findings indicate that moderate intergenerational economic support significantly enhances the health of older adults, while either minimal or excessive financial support does not demonstrate the same positive effect. Additionally, subjective life expectancy plays a mediating role between intergenerational economic support and the health of older adults, further emphasizing the beneficial impact of economic support.DiscussionThe study underscores the importance of moderate intergenerational economic support in improving the health of older adults amidst aging challenges. Future policies and practices should consider how to encourage and optimize such support to address the challenges of an aging society, enhance the welfare of older adults, and promote healthy aging.